Exploration on laminar flame propagation of biogas and DME mixtures up to 10 atm: Insight into effects of DME co-firing, CO2 addition and pressure. (15th July 2023) - Xi, Zhongya; Zhang, Jianguo; Li, Wei; Liu, Zundi; Shi, Xiaoxiang; Lian, Tianyou; Han, Sibo; Li, Yuyang
Highlights: Co-firing DME can effectively enhance the laminar flame propagation of biogas. Thermal effects dominate the increase of laminar burning velocity in DME co-firing. Effects of CO2 addition obey the order of thermal > chemical > dilution effects. Pressure effects of BG/DME mixtures reduce with the increasing DME content. Abstract: Biogas (BG) is an important renewable fuel from biomass feedstock with methane and carbon dioxide (CO2 ) as the main components. Its low fuel reactivity and flame stability caused by the considerable CO2 content raises the research need for the enhancement of its combustion. In this work, the laminar flame propagation of BG and DME mixtures was investigated with special attentions on the effects of DME co-firing, CO2 addition and pressure. The laminar burning velocities of BG/DME/air mixtures were measured at 298 K, varying initial pressures (1–10 atm), DME contents in fuel mixtures (0–1), CO2 contents in BG (0–0.4), and equivalence ratios (0.7–1.4). It was concluded that the laminar burning velocity can be effectively improved with the increasing DME content, moderately reduced with the increasing CO2 content, and dramatically reduced at elevated pressures. Meanwhile, a kinetic model of BG/DME combustion was developed and validated against the experimental data in both this work and literature. The modeling analysis shows that the enhanced flame propagation with DME co-firing is associated with the increased concentrations of key radicals like H, O, and OH due to the increased adiabatic flame temperatures and the enhanced DME-related pathways. On the other hand, the inhibited flame propagation with CO2 addition is associated with the decreased concentrations of key radicals. The fictitious diluent gas method was used to separate the different effects of DME co-firing and CO2 addition. The thermal effects play a more important role than the chemical effects in the increased laminar burning velocity with the DME co-firing, while the contributions to the decreased laminar burning velocities with the CO2 addition obey the order of thermal effects > chemical effects > dilution effects. Moreover, the pressure effects in the laminar flame propagation of BG/DME mixtures reduce with the increasing DME content, but remain nearly unchanged with the increasing CO2 content. This is mainly because the DME co-firing can reduce the significance of the most important chain-termination pathway, i.e., CH4 (+M) = CH3 + H (+M), while the CO2 addition does not have adequate influence.